How to Design a National Aggregated Ranking? - V. A. Bolotov; G. N. Motova; V. G. Navodnov; O. E. Ryzhakova (Высшее образование в России)
The article presents a new method of designing a national ranking of higher education institutions on the basis of aggregating all existing public national rankings. The new aggregating method MetALeague (Method of Analysis of Leagues) can help to do away with monopoly in evaluation, thus, providing room for independent evaluation of HEIs. The analysis of the current state of procedures and methods of independent evaluation of Russian HEIs in the form of rankings and databases was carried out. The suggested MetALeague method is based on the mathematical tool of the voting theory in small groups and helps to combine different independent evaluations in a single format. A possible approach to creating such a unified national ranking in the form of 10 leagues is considered and the calculation results are presented. The developed ranking methods and the obtained results can be useful for self-diagnosis and promotion of research, organizational and methodological activities of HEIs, and also when introducing a risk-oriented approach in oversight activities.